Dynamic Presentations - Powell M. Mark (Professional English)
Dynamic Presentations is an exciting new course for learners of business English who want to excel at presenting. Drawing closely on the world of communication skills training, this comprehensive programme covers everything from structuring your talk to fine-tuning your delivery, from designing your visuals to mastering your body language and from telling your own stories and anecdotes to handling the all-important question-and-answer session. Packed with tips and advice from some of the world's leading business and communication experts, Dynamic Presentations systematically develops the key language and presentation techniques you need to give an effective, professional and memorable performance. The book comes with two audio CDs, and video presentation extracts are also available on a separate DVD. The course is accompanied by full trainer's notes and a rich bank of online resources, including detailed feedback forms, available on the Cambridge website.Dynamic Presentations is part of the new Cambridge Business Skills series - a set of short courses from leading business English authors, combining communication skills training with professional language development. The author Mark Powell is a business communication skills trainer, one-to-one coach and instructional designer. A leader in the field of presentations training, in his 25-year career he has worked with many well-known international companies.